New models of quintessential inflation featuring plateau and hilltop potentials - Swagat S. Mishra; Varun Sahni (European Physical Journal C: Particles and Fields)
Abstract We introduce a new class of hilltop and plateau potentials which can successfully unify inflation and dark energy resulting in quintessential inflation (QI). Interestingly these new potentials are related through an inverse transformation. Namely, if $$V(\phi ) = V_0 \, v(\phi )$$ V ( ϕ ) = V 0 v ( ϕ ) is a plateau potential then the inverse potential $$V(\phi ) = V_0 \left[ v(\phi )\right] ^{-1}$$ V ( ϕ ) = V 0 v ( ϕ ) - 1 describes hilltop QI. A simple example is provided by the KKLT-inspired potential $$v(\phi ) = \left[\frac{M^{2n} + \phi ^{2n}}{N^{2n} + \phi ^{2n}}\right]\,$$ v ( ϕ ) = M 2 n + ϕ 2 n N 2 n + ϕ 2 n . When $$M/N \ll 1$$ M / N ≪ 1 this potential describes plateau QI, while its inverse, $$\left[ v(\phi )\right] ^{-1}$$ v ( ϕ ) - 1 describes hilltop QI. Other simple models of QI arise for the class of potentials $$V(\phi ) \sim \exp \left[\mp f(\phi )\right]$$ V ( ϕ ) ∼ exp ∓ f ( ϕ ) , where the − ( $$+$$ + ) sign is associated with a plateau (hilltop). A key feature of this new class of QI models is the near absence of small dimensionless parameters, or small mass parameters (relative to the energy scale of the Standard Model of particle physics) – which are usually associated with the presence of dark energy. A forecast for the gravitational wave background generated in these models is provided.